ICE manual of health and safety in construction - McAleenan, Ciaran; Oloke, David (ICE Publishing, 2015)
Written and edited by experienced construction industry professionals, the 'ICE Manual of Health and Safety in Construction' provides invaluable practical guidance on how hazards can be removed, controlled or managed, through all the stages of construction projects.
Previous edition: 2010.
Keywords: Construction industry -- Employees -- Health and hygiene -- Great Britain.; Construction industry -- Safety regulations -- Great Britain.; elektronické knihy; electronic books